(untitled) (Heritage, 2020)
The central subject of this paper is the electoral rights and problems, abuses and complications that occur in society and law. The beginning of the work is devoted to the definition of the term and menachisms of elections, terminological and legal meaning. The manner in which elections are conducted is also covered in this paper. The next part of the paper is based on the definition of the right to vote, the criteria for the possession of this type of rights and the classification of them by theory and practice. The part of the paper deals with the explanation of the treatment of electoral rights in case of abuse and the legislation regulating this area in the territory of the Republic of Serbia, more specifically with the norms of the current Criminal Code of the Republic of Serbia. The last part of the paper covers the empirical research of crimes against electoral rights in the territory of the Republic of Serbia over a five-year period, from 2014 to 2018. This section focuses on the number of reported, accused and convicted persons for crimes against electoral rights.